An in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material and preparation method thereof
By generating the TiC/TiB2 hard phase in situ at the neodymium iron boron sintering temperature and co-modifying the cerium-rich neodymium iron boron magnet, the problem of lack of intrinsic corrosion resistance is solved, and higher corrosion resistance and magnetism are achieved performance and reduce preparation costs.
Patent Information
- Application Number
- CN202311500323.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-11-13
AI Technical Summary
The existing cerium-rich neodymium iron boron magnets lack intrinsic resistance, limiting their application scope, and the high temperature requirements for hard phase synthesis by external doping methods increase the preparation cost.
By in situ generating TiC/TiB2 binary ceramic hard phase at NdFeB sintering temperature, synergistically modifying cerium-rich NdFeB materials to achieve grain boundary modification, avoiding the high-temperature synthesis link of external doping.
It improves the corrosion resistance and magnetic properties of cerium-rich neodymium-ferrous boron magnets, while reducing production costs and saving energy.
Smart Images

Figure CN117778872B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of permanent magnetic materials, and in particular relates to an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material and a preparation method thereof. Background Art
[0002] Cerium-rich NdFeB alloy has the advantages of high magnetism and low cost, and is widely used in information, transportation, medical treatment, electromechanical engineering, wind power discharge, national defense and other fields. The use of cerium (Ce) in magnets not only significantly reduces the cost of alloys and produces obvious economic benefits, but also promotes the balanced utilization of rare earth resources in my country, which is of great strategic significance. However, Ce is more active than Nd, which will further reduce the corrosion resistance of NdFeB, limiting its application range. In addition, the rapid development of information technology and transportation industry has intensified the demand for rare earth permanent magnet products in the fields of magnetic separators, industrial motors, mobile smart terminals, etc., highlighting the urgency and importance of overcoming the corrosion-prone shortcomings of cerium-rich NdFeB.
[0003] At present, grain boundary modification of NdFeB is one of the important ways to improve the magnetic properties or intrinsic corrosion resistance of materials. Generally speaking, when the chemical stability of grain boundary modifiers (metal and ceramic hard phases) is high, they are added to NdFeB alloys and distributed in the grain boundary area, which will significantly improve the intrinsic corrosion resistance of the material. The introduction of hard phases includes external doping and internal doping. Among them, the external doping method directly adds the separately synthesized ceramic hard phase (such as Al2O3, TiC, WC, etc.) to the NdFeB material through a powder mixing process. This method is simple to operate and easy to control, but due to the poor wettability between the external ceramic hard phase and the NdFeB matrix and grain boundary phase, it affects the sintering density and microstructure of the magnet, and thus has an adverse effect on the magnetic properties of the material. In addition, the externally doped hard phase usually needs to be synthesized and prepared under high temperature conditions, which will increase the preparation cost of corrosion-resistant cerium-rich NdFeB materials. The internal doping method modifies the neodymium by in-situ generation and precipitation of the target hard phase during the material preparation process. Iron-boron materials, this method can avoid the shortcomings of externally doped hard phases; however, as hard phases commonly used in metal materials, some carbides (such as SiC, WC, etc.) and borides (such as BN, etc.) are difficult to precipitate in situ at the sintering temperature of cerium-rich neodymium iron boron due to their high formation temperature, and are not easy to be applied in the modification of rare earth permanent magnet materials through internal doping; therefore, the in-situ generated hard phase needs to consider the electronic structure properties of its forming components and the affinity between the elements; other studies have shown that the size and distribution of the hard phase affect the modification effect; for example, compared with the hard phase of micron scale, when the modifier size is nanometer size, its grain boundary modification effect is better; it should also be pointed out that the externally doped nano-hard phase powder is easy to agglomerate, which is not conducive to fully exerting the strengthening effect of the nano-hard phase, and this disadvantage will not appear in the internal doping method; therefore, in order to improve the intrinsic corrosion resistance of cerium-rich neodymium iron boron magnets, it is necessary to find a method that can generate and precipitate nano-hard phases in situ in the grain boundaries of magnets. Summary of the invention
[0004] Aiming at the problem that the cerium-rich NdFeB magnets in the prior art lack intrinsic corrosion resistance, the present invention provides an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material and a preparation method thereof.
[0005] In order to achieve the above purpose, the technical solution adopted in this application is:
[0006] An in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material, the corrosion-resistant cerium-rich NdFeB permanent magnet is represented by: [RE x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z ]100-v[(TiC) u -(TiB2) 100-u ] v ; RE is a rare earth element for magnets, including the required element Ce and one or more of the optional elements Nd, Pr, La, Sm, and Ho, and Ce / RE ≥ 10%; x, y, and z represent the RE, (Ga, Al, Zn, Cu, Zr), and B elements in RE respectively. x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The mass ratio in the alloy, u represents (TiC) u (TiB2) 100-u The mass ratio in the mixture, v represents (TiC) u (TiB2) 100-u The mass proportion in the entire material composition system; the value ranges of x, y, z, u and v in the material composition system are as follows: 28.5 wt.% ≤ x ≤ 33.5 wt.%, 0.5 wt.% ≤ y ≤ 3.5 wt.%, 0.85 wt.% ≤ z≤ 1.05 wt.%, 5.0 wt.% ≤ u ≤ 90.0 wt.%, 0.05 wt.% ≤ v ≤ 2.95 wt.%.
[0007] A method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material, wherein the specific steps of the method for preparing the corrosion-resistant cerium-rich NdFeB permanent magnet are as follows:
[0008] Step 1: Prepare the main alloy RE according to the composition ratio x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B zThe main alloy is firstly made into a rapid solidification thin strip by melting-rapid solidification strip throwing process, and then hydrogen explosion and rough crushing are carried out; then the rough crushed RE x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The alloy chips are jet-milled to produce magnetic powder;
[0009] Step 2: According to (TiC) u -(TiB2) 100-u The components are proportioned to prepare Ti and C, B powders with a weighed purity of more than 99%; 0.1%-5% of the total mass of the Ti, C, B powders is weighed and mixed with ethanol to prepare a ball milling process control agent; the ratio of stearic acid to ethanol is 1 ml-4 ml of ethanol per 100 g of stearic acid; Ti, the ball milling process control agent and C, B powders are loaded into a vacuum ball milling tank, and the ball-to-material ratio is controlled between 8 and 40:1, and then the tank is sealed, vacuumed, filled with high-purity argon, and high-energy mechanical ball milling is performed. After the ball milling, a high-activity nanocrystalline powder of Ti encapsulated with C and B, namely, Ti-CB nanocrystalline powder, is obtained;
[0010] Step 3: Prepare the RE in step 1 x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The magnetic powder is mixed with the Ti-CB nanocrystalline powder and loaded into a vacuum tank with a ball milling process control agent, and then evacuated and filled with high-purity argon, and the powders are mixed on a ball mill to obtain a mixed powder with uniform distribution of the magnetic powder and the Ti-CB nanocrystalline powder;
[0011] Step 4: Orient the mixed powder obtained in step 3 in a magnetic field of 1.5 T-2.5 T to obtain a compact; then use a hydraulic press to isostatically press the compact to prepare a compact with uniform stress distribution;
[0012] Step 5: Place the compact prepared in step 4 into a vacuum chamber with a degree of vacuum of 1×10 -3 Pa-1×10 -4 Sintering is performed in a high vacuum sintering furnace of the order of pa; after sintering, argon gas is introduced for rapid cooling, and a high-density sintered magnet is obtained after cooling to room temperature;
[0013] Step six: perform secondary tempering heat treatment on the sintered magnet prepared in step five: first, place the sintered magnet in a vacuum heat treatment chamber for primary tempering. After the primary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature; then perform secondary tempering. After the secondary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature, thereby obtaining a corrosion-resistant cerium-rich NdFeB permanent magnet.
[0014] Preferably, in step 1, the average particle size of the magnetic powder is 1.5 μm-4.5 μm.
[0015] Preferably, in step 2, the ball milling time is 30 h-150 h, and the ball milling speed is 250 r / min-500 r / min.
[0016] Preferably, in step three, the mixing time is 1 h-3 h.
[0017] Preferably, in step 4, the magnetic field molding pressure used is in the range of 100 MPa-200 MPa; the hydraulic press pressure used is in the range of 150 MPa-300 MPa.
[0018] Preferably, in step five, the sintering temperature is 1040°C-1090°C, the sintering time is 2.5 h-4.5 h, and the argon rapid cooling rate is 200°C / min.
[0019] Preferably, in step six, the primary tempering temperature range is 830°C-900°C, and the primary tempering time is 1.5h-3.5h; the secondary tempering temperature range is 830°C-900°C, and the secondary tempering time is 1.5h-3.5h.
[0020] Compared with the prior art, the advantages and positive effects of the present invention are:
[0021] The present invention utilizes the characteristics that TiC and TiB2 compounds can be in-situ generated and synergistically modified at the sintering temperature of NdFeB, and proposes a corrosion-resistant cerium-rich NdFeB material and a preparation method thereof with TiC / TiB2 nano-hard phase synergistically modified at the grain boundaries, in which the two are in-situ precipitated to be beneficial to the densification of the material. The prepared cerium-rich NdFeB material has higher corrosion resistance and magnetism than the cerium-rich NdFeB material modified with externally added micron TiC / TiB2. At the same time, compared with the commonly used preparation method of cerium-rich NdFeB material with externally reinforced phase, the high-temperature synthesis step of the hard phase is omitted, energy is saved, and production costs are reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0023] Figure 1 The surface morphology of the magnet after electrochemical corrosion in 3.5% NaCl solution before the in-situ precipitation of TiC / TiB2 nano-hard phase and grain boundary modification in Example 1;
[0024] Figure 2 This is the surface morphology of the magnet after electrochemical corrosion in 3.5% NaCl solution after the in-situ precipitation of TiC / TiB2 nano-hard phase and grain boundary modification in Example 1. DETAILED DESCRIPTION
[0025] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0027] Embodiment 1, as Figure 1 , Figure 2 As shown, an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material of the present application is characterized in that the corrosion-resistant cerium-rich NdFeB permanent magnet is composed of: [RE x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z ]100-v[(TiC) u -(TiB2) 100-u ] v ; RE is a rare earth element for magnets, including the required element Ce and one or more of the optional elements Nd, Pr, La, Sm, and Ho, and Ce / RE ≥ 10%; x, y, and z represent the RE, (Ga, Al, Zn, Cu, Zr), and B elements in RE respectively. x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The mass ratio in the alloy, u represents (TiC) u (TiB2) 100-u The mass ratio in the mixture, v represents (TiC) u (TiB2) 100-uThe mass proportion in the entire material composition system; the value ranges of x, y, z, u and v in the material composition system are as follows: 28.5 wt.% ≤ x ≤ 33.5 wt.%, 0.5wt.% ≤ y ≤ 3.5 wt.%, 0.85 wt.% ≤ z ≤ 1.05 wt.%, 5.0 wt.% ≤ u ≤ 90.0 wt.%, 0.05 wt.% ≤ v ≤ 2.95 wt.%.
[0028] The present invention discloses a method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material, and the specific steps are as follows:
[0029] Step 1: Prepare the main alloy RE according to the composition ratio x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The main alloy is firstly made into a rapid solidification thin strip by melting-rapid solidification strip throwing process, and then hydrogen explosion and rough crushing are carried out; then the rough crushed RE x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The alloy chips are jet-milled to prepare magnetic powder, wherein the average particle size of the magnetic powder is controlled between 1.5 μm and 4.5 μm;
[0030] Step 2: According to (TiC) u -(TiB2) 100-u Preparation of Ti and C, B powders with a purity of more than 99% by component ratio: 0.1%-5% of the total mass of Ti, C, B powders are weighed and mixed with ethanol to prepare a ball milling process control agent; the ratio of stearic acid to ethanol is 1 ml-4 ml of ethanol per 100 g of stearic acid; Ti, C, B powders are loaded into a vacuum ball milling jar, and the ball-to-material ratio is controlled to be 12:1; then the jar is sealed, vacuumed, and filled with high-purity argon for high-energy mechanical ball milling, the ball milling time is 60 h, and the ball milling speed is 300 r / min; after the ball milling, a high-activity nanocrystalline powder of Ti encapsulated with C and B, namely Ti-CB nanocrystalline powder, is obtained;
[0031] Step 3: Prepare the RE in step 1 x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The magnetic powder is mixed with the Ti-CB nanocrystalline powder and placed in a vacuum tank with a ball milling process control agent, and then evacuated and filled with high-purity argon, and the powder is mixed on a ball mill for 1.5 hours; after the powder mixing is completed, a mixed powder with uniform distribution of the magnetic powder and the Ti-CB nanocrystalline powder is obtained;
[0032] Step 4: Orient the mixed powder obtained in step 3 in a magnetic field of 1.5 T-2.5 T, and control the molding pressure range to be 100 MPa-200 MPa to obtain a compact; then, use a hydraulic press to isostatically press the compact, and the hydraulic press pressure is 200 MPa to prepare a compact with uniform stress distribution;
[0033] Step 5: Place the compact prepared in step 4 into a vacuum chamber with a degree of vacuum of 1×10 -4 The sintering was carried out in a high vacuum sintering furnace of the order of pa, the sintering temperature was 1050 ℃, and the sintering time was 3 h; after the sintering was completed, argon gas was introduced for rapid cooling, and the cooling rate was 200 ℃ / min; after cooling to room temperature, a high-density sintered magnet was obtained;
[0034] Step 6: Perform secondary tempering heat treatment on the sintered magnet prepared in step 5: first, place the sintered magnet in a vacuum heat treatment for primary tempering, the primary tempering temperature is 880 ° C, and the primary tempering time is 2.5 h; after the primary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature; then perform secondary tempering, the secondary tempering temperature is 690 ° C, and the secondary tempering time is 2.5 h; after the secondary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature, and a corrosion-resistant cerium-rich NdFeB permanent magnet is obtained;
[0035] The prepared corrosion-resistant cerium-rich NdFeB permanent magnet was placed in an open-circuit PFM permanent magnet material measurement system, and the magnetic properties were measured as follows: r =13.3 kG, H cj =12 kOe, (BH) max =42 MGOe.
[0036] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material, characterized in that: The modified cerium-rich NdFeB material is composed of: x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z ] 100-v [(TiC) u (TiB2) 100-u ] v ; RE is a rare earth element for magnets, including the required element Ce and one or more of the optional elements Nd, Pr, La, Sm, and Ho, and Ce / RE ≥ 10%; x, y, and z represent the RE, (Ga, Al, Zn, Cu, Zr), and B elements in RE respectively. x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The mass ratio in the alloy, u represents (TiC) u (TiB2) 100-u The mass ratio in the mixture, v represents (TiC) u (TiB2) 100-u The mass proportion in the entire material composition system; the value ranges of x, y, z, u and v in the material composition system are as follows: 28.5 wt.% ≤ x ≤ 33.5 wt.%, 0.5 wt.% ≤ y ≤ 3.5 wt.%, 0.85 wt.% ≤ z ≤ 1.05 wt.%, 5.0 wt.% ≤ u ≤ 90.0 wt.%, 0.05 wt.% ≤ v ≤ 2.95wt.% The specific steps of the modified cerium-rich NdFeB material preparation method are as follows: Step 1: Prepare the main alloy RE according to the composition ratio x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The main alloy is firstly made into a rapid solidification thin strip by melting-rapid solidification strip throwing process, and then hydrogen explosion and rough crushing are carried out; then the rough crushed RE x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The alloy chips are jet-milled to produce magnetic powder; Step 2: According to (TiC) u (TiB2) 100-u The components are proportioned to prepare Ti and C, B powders with a weighed purity of more than 99%; 0.1%-5% of the total mass of the Ti, C, B powders is weighed and mixed with ethanol to prepare a ball milling process control agent; the ratio of stearic acid to ethanol is 1 ml-4 ml of ethanol per 100 g of stearic acid; Ti, the ball milling process control agent and C, B powders are loaded into a vacuum ball milling tank, and the ball-to-material ratio is controlled between 8 and 40:1, and then the tank is sealed, vacuumed, filled with high-purity argon, and high-energy mechanical ball milling is performed. After the ball milling, a high-activity nanocrystalline powder of Ti encapsulated with C and B, namely, Ti-CB nanocrystalline powder, is obtained; Step 3: Prepare the RE in step 1 x (Ga,Al,Zn,Cu,Zr) y Fe 100-x-y-z B z The magnetic powder is mixed with the Ti-CB nanocrystalline powder and loaded into a vacuum tank with a ball milling process control agent, and then evacuated and filled with high-purity argon, and the powders are mixed on a ball mill to obtain a mixed powder with uniform distribution of the magnetic powder and the Ti-CB nanocrystalline powder; Step 4: Orient the mixed powder obtained in step 3 in a magnetic field of 1.5 T-2.5 T to obtain a compact; then use a hydraulic press to isostatically press the compact to prepare a compact with uniform stress distribution; Step 5: Place the compact prepared in step 4 into a vacuum chamber with a degree of vacuum of 1×10 -3 Pa~1×10 -4 Sintering is performed in a high vacuum sintering furnace of the order of Pa; after sintering, argon gas is introduced for rapid cooling, and a high-density sintered magnet is obtained after cooling to room temperature; Step six: perform secondary tempering heat treatment on the sintered magnet prepared in step five: first, place the sintered magnet in a vacuum heat treatment chamber for primary tempering. After the primary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature; then perform secondary tempering. After the secondary tempering heating is completed, argon gas is introduced into the furnace to quickly cool the magnet to room temperature to obtain a modified cerium-rich NdFeB material.
2. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step 1, the average particle size of the magnetic powder is 1.5 μm-4.5 μm.
3. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step 2, the ball milling time is 30 h-150 h, and the ball milling speed is 250 r / min-500 r / min.
4. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step 3, the mixing time is 1 h-3 h.
5. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step 4, the magnetic field molding pressure used ranges from 100 MPa to 200 MPa; the hydraulic press pressure used ranges from 150 MPa to 300 MPa.
6. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step five, the sintering temperature is 1040°C-1090°C, the sintering time is 2.5 h-4.5 h, and the argon rapid cooling rate is 200°C / min.
7. The method for preparing an in-situ TiC / TiB2 binary ceramic hard phase grain boundary modified cerium-rich NdFeB material according to claim 1, characterized in that: In step six, the primary tempering temperature range is 830 ℃-900 ℃, and the primary tempering time is 1.5 h-3.5 h; the secondary tempering temperature range is 690 ℃, and the secondary tempering time is 1.5 h-3.5 h.
Citation Information
Patent Citations
In-situ precipitated TiC nano hard-phase strengthened net-shaped copper-titanium composite material and preparation method thereof
CN105483413A
Cited By
Special low-cost cerium-rich neodymium iron boron permanent magnet material for smart home motor as well as preparation method and application of permanent magnet material
CN122370163A